Pengaruh Model Time Token Terhadap Keterampilan Berbicara Siswa Kelas IV SDN Prayitna Kecamatan Praya - Mardhiyati Wira Hamdini; Khairunnisa Khairunnisa; Heri Setiawan (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
This research aims to discover the effect of Time Token on the speaking skill of fourth grade IV students of Prayitna Elementary School. The type of this research is experimental study with repeated treatment research design. The subject of this study is the fourth grade students of Prayitna Elementary School. The methods of data collection are observation and speaking skill test. The speaking skill test is used to gain the data related to the speaking skill of the students while the observation is used to obtain the compliance data done by the teachers. Then the data obtained were analyzed by using anova repeated measure’s formula in order to find out whether there is an effect of the storytelling method through media of picture to the speaking skill of the students. The result of this study shows the significant numbers in 0,000 and that means it is smaller than 0.05. This study implies that Ho is rejected and Ha is received. It can be concluded that the storytelling method that showed through the media of picture can give an effect to the speaking skill of fourth grade students of Prayitna Elementary School for 2020/2021 period.